Evaluation of adaptive capabilities of students of different nationalities: cross sectional study - Varsha Priyadarshani, Mohotti Gedara Weerakoon Mudiyanselage; Wattaladeniya, Poorna Gayan; Dzmitry, Karnialiuk; Anbalagan, Shailesh; Kalna Munasinghe, Owini (International Journal of Research in Medical Sciences, 2024)
Background: The autonomic nervous system actively regulates the body’s reactions to various external and internal factors, ensuring physiological balance in a person. Advances in information technology now allow for a dependable and non-intrusive examination of this system through an in-depth analysis of heart rate variability. This approach is not only a recognized instrument in cardiac studies but is also growing in its utilization for numerous clinical purposes. This overview details the foundational theories and practical uses of this evolving method. The purpose of the study is to study the adaptive reserves and indicators of autonomic regulation in students of different nationalities. Methods: We conducted a cross sectional study of 110 students studying in Grodno State Medical University using photoplethysmography method via an app “Pulse HRV”during the period of December 2022- February 2023. The students were grouped into three groups: Group 1 being Southeast Asian students, Group 2 being Nigerian students and Group 3 being Belarussian students. Results: As a result of the analysis, it was found that AP in group 2 was significantly different from groups 1 and 3. At the same time endurance coefficient was above norm in all groups, which indicated a weakening of the cardiovascular system, while in students from group 2 it was significantly less than in groups 1 and 3. Conclusions: Students from Nigeria have significantly higher adaptive reserves than students from Belarus and Southeast Asia, which may be due to the prevalence of increased tone of the parasympathetic nervous system.